Enhancing Local Chinese Language Teacher Training in the Republic of the Congo - Ngatseke Mampola Freud Savinien (Published by Confucius Institute UNS, 2023)
China is now one the most important countries in the globe, and with the increasing influence of Chinese language and culture, Chinese education has become more and more important during the last two decades in Africa in general, and in the Republic of Congo in particular. However, we assert the existence a major flaw in the field of Chinese education, mainly the lack of adequate training programs for Chinese teachers. Thus, this study investigates the current situation of local Chinese teacher training in the Republic of the Congo, with to goal to identify the main challenges related to the issue, and to put forward innovative methods to solve these challenges. Lately, Chinese teaching in the Republic of Congo has developed rapidly. Looking into the future, this research outlines the future research direction in the field of Chinese teacher training. It emphasizes the potential long-term impact of intensive training on language education, cultural exchanges and economic opportunities for Congolese students. In addition, it emphasizes the role can be played by government agencies, educational institutions and international organizations in supporting such initiatives.